Chemical composition and antimicrobial activity of essential oil extracted from pomelo (Citrus maxima (Burm.) Merr.) - Huỳnh , Xuân Phong; Lưu , Minh Châu; Trần, Thị Xuân Nghi; Nguyễn, Ngọc Thạnh; Bùi, Hoàng Đăng Long; Bạch, Long Giang; Nguyễn, Văn Mười; Trần, Thanh Trúc (Hue University Journal of Science: Natural Science, 2021)
Pomelo is a Vietnam’s plant species with high nutritional and economic value. Besides, pomelo essential oil contains numerous compounds with high biological activity. The essential oil is extracted by using steam distillation, and its chemical composition is determined by means of GC-MS. The major components are limonene (91.19%), b-myrcene (2.92%), a-phellandrene (1.98%), and a-pinene (1.19%). The antimicrobial activity of essential oils is tested against pathogenic Gram-positive bacteria (Bacillus cereus, Staphylococcus aureus), Gram-negative bacteria (Escherichia coli), and Aspergillus flavus at different concentrations with the agar well diffusion method. This essential oil is active against B. cereus, S. aureus, and E. coli with inhibition diameter zones at 8.3–11.3, 10.3–18.7, and 9.0–11.7 mm, respectively, and inhibits A. flavus mold with 18.9–65.0% efficiency.